Tinjauan Hukum Pidana Terhadap Tindakan Malpraktek dalam Bidang Kesehatan atau Medis - Gunawan, Aria Chandra; Yudanto, Dika; Junaidi, Amir (Universitas Ekasakti, 2023)
Malpractice, a criminal act in the healthcare field, creates legal problems when patients realize the impact. Medical negligence can harm patients, triggering risks that could have been avoided with medical prudence. Normative and sociological research supports the criminal law assessment of malpractice, focusing on maltreatment and negligence causing death. Sanctions are imposed by the medical professional organization and the immediate supervisor in charge, taking into account the ethical values and values of the profession. Punishment is only imposed if the act violates the law, and the form of malpractice needs to be adjusted to the development of science and the times.